463. OESOPHAGEAL PERFORATIONS: CAUSES, MANAGEMENT, AND OUTCOMES AT A SPECIALIST UPPER GASTROINTESTINAL UNIT OVER A TEN-YEAR PERIOD. (24th September 2022) - Toi, Teri; Lam, Stephen; Kumar, Bhaskar
Abstract: Perforation of the oesophagus is a relatively rare but life-threatening condition, which requires early laparoscopic or surgical intervention. The aim of this work was to describe the causes, management and outcomes of emergency patients treated at a single high volume upper gastrointestinal specialist unit in the United Kingdom. In this retrospective case series, we identified all patients who presented to a tertiary upper gastrointestinal surgery unit with a spontaneous or iatrogenic oesophageal perforation. Patient demographics, clinical management, and outcomes were identified by hand review of the medical notes. Between March 2011 to July 2020, 58 patients were identified. The median age was 71 years (interquartile range 52 years to 83 years) and 64% were male. A total of 83% of patients had benign perforations, the rest being malignant. Management of all patients was supportive in 41%, endoscopic in 19% and surgical in 40%. In total 63% of spontaneous benign perforations were managed surgically, and only 6% endoscopically. The median length of hospital stay for all patients that survived more than 90 days was 13 days. The 90-day mortality rate for all patients was 42%. Oesophageal perforations are a relatively rare but lethal disease, carrying a mortality. Whilst surgery has historically been the most common management of benign spontaneous perforations, endoscopic treatments are likely to become increasingly common in the future.